2013
DOI: 10.1177/1087054712473833
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Behavioral Ratings of Inattention, Impulsivity, and Hyperactivity in Children

Abstract: Many of the behaviors related to inattention strongly predicted reading fluency, reading comprehension, and overall reading ability. Boys who exhibited inattentive behaviors performed more poorly on reading comprehension measures than girls with inattentive behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 17 publications
8
35
0
2
Order By: Relevance
“…Only IN was independently associated with concurrent and future academic difficulties, suggesting that the significant bivariate association between HI and academic impairment is explained by variance shared with IN rather than a unique association with HI per se. This pattern of results is highly consistent with earlier cross-sectional studies of various academic measures (see review by Willcutt et al, 2012) and underscores the unique importance of early IN symptoms as predictors of reading difficulties in early (Dittman, 2016) and middle (Pham, 2016) elementary school and critical targets for early identification and intervention. Furthermore, the significant cross-lagged paths from earlier overall impairment, and especially academic impairment, to IN may reflect the effects of early academic demands on IN behaviors (Brosco & Bona, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Only IN was independently associated with concurrent and future academic difficulties, suggesting that the significant bivariate association between HI and academic impairment is explained by variance shared with IN rather than a unique association with HI per se. This pattern of results is highly consistent with earlier cross-sectional studies of various academic measures (see review by Willcutt et al, 2012) and underscores the unique importance of early IN symptoms as predictors of reading difficulties in early (Dittman, 2016) and middle (Pham, 2016) elementary school and critical targets for early identification and intervention. Furthermore, the significant cross-lagged paths from earlier overall impairment, and especially academic impairment, to IN may reflect the effects of early academic demands on IN behaviors (Brosco & Bona, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Longitudinal research at early ages has provided robust support for these (Scarborough, 1998; Schatschneider, Fletcher, Francis, Carlson, & Foorman, 2004) and other language skills (e.g., vocabulary, print awareness, letter identification, and decoding) as important early predictors of reading (Anthony & Lonigan, 2004; Burgess & Lonigan, 1998; Leppänen, Aunola, Niemi, & Nurmi, 2008). Domain general predictors such as working memory (Savage, Lavers, & Pillay, 2007; Siegel & Ryan, 1989), processing speed (Shanahan et al, 2006; Willcutt et al, 2008), and attention (Grills-Taquechel, Fletcher, Vaughn, Denton, & Taylor, 2013; Pham, 2016) also contribute to early reading. Predictors relate differentially to reading outcomes: rapid naming and processing speed are more related to reading fluency (Georgiou, Kirby, Parrila, & Stephenson, 2008; Wolf, Bowers, & Biddle, 2000), whereas working memory is more strongly linked with comprehension (Cain, Oakhill, & Bryant, 2004; Carretti, Borella, Cornoldi, & De Beni, 2009).…”
Section: Reading Predictorsmentioning
confidence: 99%
“…The ability to read fluently in the early grades is also predictive of high-stakes achievement test scores in elementary and middle school, and continues to predict reading comprehension scores into adulthood ( Baker et al, 2014 ; Tighe & Schatschneider, 2014 ). There is some evidence that reading fluency is linked to attention, in that inattentive behavior is a predictor of poor reading fluency outcomes in typical developing school children ( Pham, 2013 ). A study using a community sample of elementary school children found that mid-term teacher-rated inattention predicted word reading fluency at the end of the same year, although it did not predict basic reading (word reading without timed component and decoding ability) ( Grills-Taquechel et al, 2013 ).…”
mentioning
confidence: 99%